CONTRIBUTION OF WRIST FLEXIBILITY AND ARM MUSCLE POWER TO SHOOTING RESULTS IN HANDBALL AT PELATDA DKI JAKARTA ATHLETES - Arif, Muhamad; Sukriadi, Slamet; Fadillah, Bazuri (JUARA : Jurnal Olahraga, 2024)
The purpose of this study was to obtain information about the Contribution of Wrist Flexibility and Arm Muscle Power to Shooting Results in Handball Games in PELATDA DKI Jakarta Athletes. The method used is descriptive method. The study population was PELATDA DKI Jakarta athletes of 20 people using a total sampling technique of 20 people. The data collection technique was by carrying out arm muscle power tests using a medicine ball, wrist flexibility tests using a goniometer and shooting tests on the right and left sides. The data analysis used was multiple linear regression analysis with the SPSS 25 program. The results showed that there was a contribution of arm muscle power to shooting Handball in PELATDA DKI Jakarta Athletes of 0.793, which means that this contribution has a strong relationship, then the contribution of wrist flexibility to shooting Handball for PELATDA DKI Jakarta Athletes was 0.619 which means that this contribution also has a strong relationship and a more dominant contribution, namely arm muscle power compared to the contribution of wrist flexibility to shooting Handball for PELATDA DKI Jakarta Athletes.